2007
DOI: 10.1111/j.1651-2227.2007.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the educational impact of the WHO Essential Newborn Care course in Zambia

Abstract: We found significant improvements in trainees' knowledge and skills in essential newborn care following the WHO ENC course; however, lack of basic resources may have limited the application of the ENC guidelines. Implementation of the ENC course should be undertaken in consideration with the local conditions available for newborn care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 6 publications
3
54
0
Order By: Relevance
“…Our findings are consistent with a study in Zambia that reports significant improvement in healthcare providers' knowledge and skills following curriculum intervention despite a limited application of curriculum guidelines due to local conditions [16]. Although NRP training reduces neonatal mortality in controlled, nonrandomized studies in China, India, and Africa [10, 15, 32, 33], the literature surrounding NRP curriculums' impact is not consistent.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are consistent with a study in Zambia that reports significant improvement in healthcare providers' knowledge and skills following curriculum intervention despite a limited application of curriculum guidelines due to local conditions [16]. Although NRP training reduces neonatal mortality in controlled, nonrandomized studies in China, India, and Africa [10, 15, 32, 33], the literature surrounding NRP curriculums' impact is not consistent.…”
Section: Discussionsupporting
confidence: 82%
“…NRP is the developed world's standard of care to prevent death and complications of cerebral palsy due to asphyxia [13], and, when systematically implemented by trained personnel, has the potential to annually prevent 192 000 intrapartum-related neonatal deaths worldwide and 5–10% of deaths related to preterm complications [14]. Curriculums with components of NRP have significantly improved healthcare providers' knowledge, skills, and attitudes in developing countries [15, 16] and decreased neonatal mortality in the developing world up to 65.7 percent [10, 17, 18]. One study revealed declines in national trends of neonatal mortality over an 8-year period following NRP integration across Malaysia [19].…”
Section: Introductionmentioning
confidence: 99%
“…These educational materials provide evidencebased guidelines for routine care and initial management of neonates during the first week after birth. 6 A major barrier to action on neonatal health has been the erroneous perception that only expensive, highly technological care can reduce mortality. 7,8 Several of the interventions that could reduce neonatal mortality (resuscitation only, exclusive breastfeeding only, and ENC that includes resuscitation and breastfeeding) are relatively inexpensive.…”
mentioning
confidence: 99%
“…Use of a self administered, computer based course was found to be equally successful in increasing relevant knowledge as the conventional face to face course in South African and Zambian studies. [17] In developing countries resources generally lack and the lower cost of a teleeducation course in this critical field can allow much greater dissemination of relevant knowledge, for a given amount of funds.…”
Section: Teleeducation For Nurses In Africamentioning
confidence: 99%